(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To identify the types of cancer, the proportion of late-diagnosed cases, and associated factors at Ca Mau General Hospital from 2023 to 2024. Subjects and methods: A cross-sectional descriptive study was conducted on 995 patients newly diagnosed with cancer from January 2023 to December 2024. Data were collected from the hospital’s management system. Univariate and multivariate analyses were performed using STATA 18.0 to identify associated factors. Results: The most common cancer types were breast cancer (26.5%), lung cancer (21.21%), liver and biliary tract cancer (20.68%), and colorectal cancer (19.07%). The proportion of late-diagnosed cancer cases was 65.63%. Logistic regression analysis identified factors associated with increased odds of late diagnosis, including rural residence (OR = 2.46, 95% CI: 1.33-4.74), education below high school level (OR = 1.43, 95% CI: 1.15-2.74), income less than 5 million VND/month (OR = 1.61, 95% CI: 1.21-2.31), delayed time from symptom onset to medical consultation (OR = 1.42, 95% CI: 1.15-2.36), lack of regular health check-ups (OR = 1.62, 95% CI: 1.24-2.42), and delayed diagnosis by healthcare facilities (OR = 1.53, 95% CI: 1.11-2.23). Conclusion: The most frequently diagnosed cancers at Ca Mau General Hospital were breast, bronchopulmonary, hepatobiliary, and colorectal cancers, with a high rate of late diagnosis at Ca Mau General Hospital. Key risk factors for late diagnosis included rural residence, education below high school level, low income (< 5 million VND/month), delayed consultation after symptom onset, lack of regular health check-ups, and delayed diagnosis by healthcare facilities.